2015
DOI: 10.5761/atcs.oa.15-00126
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of VATS Lobectomy for Elderly Non-Small Cell Lung Cancer: A Propensity Score-Matched Study

Abstract: Purpose: To analyze the short-term and long-term outcome of video-assisted thoracic surgery (VATS) lobectomy for elderly patients with non-small cell lung cancer. Methods: 105 patients aged ≥75 years with resected non-small cell lung cancer were matched with 105 younger patients by propensity score. Survival rates were calculated by the Kaplan-Meier method. The cumulative incidence functions of conditional survival rate according to the age of the patients were calculated by competing risk analysis. Results: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
2
6
0
4
Order By: Relevance
“…The VATS approach obviates the need for division of chest wall muscles or rib spreading. Advocates for VATS lobectomy have previously emphasized the benefits of decreased post‐operative pain, early chest tube removal and shorter hospital stay . In the present study, we observed a significantly shorter mean hospital length of stay in the VATS group compared with the OT group.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The VATS approach obviates the need for division of chest wall muscles or rib spreading. Advocates for VATS lobectomy have previously emphasized the benefits of decreased post‐operative pain, early chest tube removal and shorter hospital stay . In the present study, we observed a significantly shorter mean hospital length of stay in the VATS group compared with the OT group.…”
Section: Discussionsupporting
confidence: 59%
“…Lung resection surgery in the elderly can be problematic due to frailty, multiple comorbidities and poor pulmonary reserve, resulting in higher rates of post‐operative morbidity . Early mortality after lung resection in elderly patients has improved in recent decades, ranging from 0% to 4.8% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Các thông tin cần thu thập: [6]). Tiến tới chúng tôi thực hiện phẫu thuật nội soi cắt thuỳ phổi 1 lỗ, đây cũng là tiến bộ vượt bậc trong PTNSLN.…”
Section: Phương Pháp Thu Thập Thông Tinunclassified
“…However, there are few studies on VATS lobectomy in elderly NSCLC patients, and majority of them only report short-term outcomes [29][30][31][32][33][34][35][36][37]. This study aimed to compare the e cacy of VATS lobectomy in elderly versus non-elderly NSCLC patients in order to explore the short-and long-term outcomes of VATS lobectomy in elderly NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%